(untitled) (Research, Society and Development, 2024)
Objective: To analyze how health education actions impact blood donor recruitment. Methodology: This is an integrative review, supported by the PICo strategy, conducted in the BVS, LILACS, and BNENF databases, using the descriptors "Health Education" and "Blood Donors" with the Boolean operator AND, during the period of April to May 2024. The search resulted in 385 documents, which, after applying filters for full text, articles, Portuguese language, and the chronological cut of the years 2018 to 2023, resulted in 08 articles. Results: The reading of the articles allowed the identification of a limited number of studies on the subject, which were developed for diverse audiences. Regarding the main topics addressed, two thematic categories were constructed: "Blood Donation and Its Fundamental Aspects in Donor Recruitment" and "Health Education in Blood Donor Recruitment." Conclusion: It is essential to create opportunities for health education activities, with a critical perspective in the construction of knowledge about blood donation, demystifying existing fears, myths, and prejudices.